Human preferences for colorful birds: Vivid colors or pattern? - Lišková, Silvie; Landová, Eva; Frynta, Daniel (Evolutionary psychology, 2015)
In a previous study, we found that the shape of a bird, rather than its color, plays a major role in the determination of human preferences. Thus, in the present study, we asked whether the preferences of human respondents towards uniformly shaped, colorful birds are determined by pattern rather than color. The experimental stimuli were pictures of small passerine birds of the family Pittidae possessing uniform shape but vivid coloration. We asked 200 participants to rank 43 colored and 43 identical, but grayscaled, pictures of birds. To find the traits determining human preferences, we performed GLM analysis in which we tried to explain the mean preference ranks and PC axes by the following explanatory variables: the overall lightness and saturation, edges (pattern), and the portion of each of the basic color hues. The results showed that the mean preference ranks of the grayscale set is explained mostly by the birds' pattern, whereas the colored set ranking is mostly determined by the overall lightness. The effect of colors was weaker, but still significant, and revealed that people liked blue and green birds. We found no significant role of the color red, the perception of which was acquired relatively recently in evolution.
Keywords: Animals; Emotions; zrak; Birds; Female; barva; Color Perception; ženské pohlaví; emoce; vnímání barev; lidé; Color; světelná stimulace; Photic Stimulation; Esthetics; ptáci; Male; Choice Behavior; výběrové chování; zvířata; mužské pohlaví; estetika; Vision, Ocular; Humans